2015
DOI: 10.1111/tri.12573
|View full text |Cite
|
Sign up to set email alerts
|

Should ABO-incompatible deceased liver transplantation be reconsidered?

Abstract: In this issue of Transplant International, two separate groups, one from China and one from northern Europe, present their retrospective experiences and results in ABOincompatible (ABOin) deceased donor liver transplantation (DDLT) in adult recipients [1,2]. Both groups conclude that ABOin DDLT might be life-saving and might be used in urgent cases.In the study by the Sun Yat-sen University group from Guangzhou, China [2], in a population of recipients suffering from acute hepatitis B virus liver failure, ABOi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…The acceptance of donor-recipient AB0 blood group incompatibility was initially limited largely to the extreme circumstances of patients with an urgent need for LT. The initial results were unsatisfactory, with high rates of rejection, HA thrombosis, biliary complications, sepsis, and other causes of graft and patient loss [ 5 , 7 , 8 , 9 , 10 ]. It has been previously noted, however, that the results of AB0i LT are better in children than in adults and are better still in the youngest children, less than one year old at transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acceptance of donor-recipient AB0 blood group incompatibility was initially limited largely to the extreme circumstances of patients with an urgent need for LT. The initial results were unsatisfactory, with high rates of rejection, HA thrombosis, biliary complications, sepsis, and other causes of graft and patient loss [ 5 , 7 , 8 , 9 , 10 ]. It has been previously noted, however, that the results of AB0i LT are better in children than in adults and are better still in the youngest children, less than one year old at transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…During our study period, several protocols of pre-transplant desensitization were developed internationally in an attempt to prevent early or immediate humoral rejection and to improve late results after AB0i LT: splenectomy, plasma exchange, immunoadsorption, high-dose intravenous immunoglobulins (IVIG), and antiCD20 monoclonal antibodies (rituximab) [ 7 , 8 , 9 , 11 , 13 , 14 , 15 , 16 , 17 , 18 ]. We found that the pre-transplant desensitization of children before AB0i LT was very uncommon in European centers, with high-dose IVIG being given more often than alternatives but only in 8% of recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic artery thrombosis occurred in 24% of ABOi allografts [3,28]. The metaanalysis of Wu et al [2] in 2011 showed the total complication incidence and acute rejection incidence to be higher after ABOi LDLT than after ABOc LT. Lee at al.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns have been raised that deceased donor ABOi LT is ethically problematic in the context of its proven inferior graft survival combined with long waiting lists for liver transplantation at most centers around the World 222,307 . The situation with LDLT ABOi LT is of course a different entity where the procedure is justified when no ABOc living donor is available.…”
Section: Ethical Considerationsmentioning
confidence: 99%